Identification and speciation of Malassezia in patients clinically suspected of having pityriasis versicolor - Avani Shah; Avani Koticha; Milind Ubale; Shashir Wanjare; Preeti Mehta; Uday Khopkar (Wolters Kluwer Medknow Publications, 2013)
Background: Malassezia is a lipid-dependent yeast known to cause Pityriasis versicolor, a chronic, recurrent superficial infection of skin and present as hypopigmented or hyperpigmented lesions on areas of skin. If not diagnosed and treated, it may lead to disfigurement of the areas involved and also result in deep invasive infections. Aim: The aim of the present study was to identify and speciate Malassezia in patients clinically suspected of having Pityriasis versicolor. Materials and Methods: Total 139 patients suspected of having Pityriasis versicolor were evaluated clinically and diagnosis was done by Wood's lamp examination, confirmed mycologically by using KOH, cultivation on Sabouraud's dextrose agar and modified Dixon agar at a tertiary care hospital in Mumbai. The total duration of study was 12 months. Results: Majority of the patients were males (59.71%) in the age group of 21-30 years (33.81%) who were students (30.21%) by profession. The incidence of Malassezia in Pityriasis versicolor was 50.35%. The most common isolate was M. globosa (48.57%), followed by M. furfur (34.28%). Majority of the patients had hypopigmented lesions, with M. globosa as the predominant isolate. Neck was the most common site affected; 88.48% were Wood's lamp positive of which 56.91% of Malassezia isolates grew on culture. KOH mount was positive in 82.01% of which 61.40% Malassezia isolates grew on culture. Conclusions: The procedure of culture and antifungal testing is required to be performed as different species of Malassezia are involved in Pityriasis versicolor and susceptibility is different among different species. Thus, it would help to prevent recurrences and any systemic complications.